Antioxidant activity of dairy mixtures for child nutrition - Tarun, Ekaterina I.; Yushkevich, Mariya A. (Journal of the Belarusian State University. Ecology, 2020)
The comparative study of the antioxidant activity of dairy mixtures for child nutrition was conducted. Fluorescein fluorescence intensity dependencies are obtained on the logarithm of the concentration of infant formula, from which IC50 values are graphically determined. A suppression of the action of free radicals and an increase in fluorescence of fluorescein up to 78−96 % with a concentration of samples of 0,5 mg / ml are observed. The maximum antioxidant activity (AOA) was obtained for the «NAN Optipro 1+» milk formula, with an IC 50 of 0,58 ∙ 10 -2 mg (protein)/ ml. The minimum IC 50 based on dry matter (5,89-6,03 ∙ 10 -2 mg / ml) was obtained for the milk mixtures «NAN Optipro HA 1+», «NAN Optipro 1+» and «HA hypoallergenic 3+».